ADSORPTION OF WATER AND BENZENE VAPOUR IN MESOPOROUS MATERIALS - Paulina, Paulina (UI Scholars Hub, 2008)
Mesoporous materials have attracted the attention of many researchers due to the potential applications promised by the materials. This article discusses adsorption of water and benzene vapour in mesoporous materials (mesoporous silica: MCM-41, MCM-48 and their modification). MCM-41 and MCM-48 were synthesized hydrothermally at 100 o C using cethyltrimethylammonium chloride or dodecyltrimethylammonium bromide for MCM-41 (C16) or MCM-41 (C12) respectively and a mixture of cethyltrimethylammonium bromide and Triton X-100 for MCM-48 as templates. Their modifications were conducted by silylation of MCM-41 (C16) and MCM-48 with trimethylchloro silane (MCM16- TMCS and MCM48-TMCS) and t-butyldimethylchloro silane (MCM16-TBDMCS and MCM48-TBDMCS). Results showed that MCM-41 and MCM-48 materials had hydrophobic features which were shown in the small amount of water adsorption at low P/P0 . The hydrophobicity of samples used in this study decrease in the sequence: MCM-41 (C16) > MCM-48 > MCM-41 (C12). The hydrophobicity increased when MCM-41 and MCM-48 were silylated with TMCS or TBDMCS. All unsilylated MCM materials show higher affinity to benzene at low P/P0 than the silylated samples. The results of water and benzene adsorption showed that silylated samples are promising candidates as selective adsorbents for organic compounds.